The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ppul.25699
|View full text |Cite
|
Sign up to set email alerts
|

Management of parapneumonic pleural effusion in children: Is there a role for corticosteroids when conventional nonsurgical management fails? A single‐center 15‐year experience

Abstract: Objective: Description of the use of corticosteroids for the management of parapneumonic pleural effusion in children.Methods: Retrospective single-center observational study of all children hospitalized with a diagnosis of parapneumonic pleural effusion during a 15-year period.Results: We documented 97 cases of parapneumonic effusion during the study period, with a median age (interquartile range [IQR]) of 43 (33-61) months. Most of the children benefited from an evacuation of the pleural effusion (89/97, 91.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Although it is often interpreted as a sign of treatment failure, it may also be due to underlying inflammation, prompting the addition of corticosteroids to the treatment. 10,11 In conclusion, this study adds weight to others [6][7][8]12 suggesting that restricting the use of pleural drainage is safe and does not prolong LOS, which may be more conditioned by the routines at each center.…”
Section: Discussionmentioning
confidence: 63%
“…Although it is often interpreted as a sign of treatment failure, it may also be due to underlying inflammation, prompting the addition of corticosteroids to the treatment. 10,11 In conclusion, this study adds weight to others [6][7][8]12 suggesting that restricting the use of pleural drainage is safe and does not prolong LOS, which may be more conditioned by the routines at each center.…”
Section: Discussionmentioning
confidence: 63%
“…However, the attenuation of the cytokine-triggered inflammatory process seems a reasonable approach as an adjunctive treatment. Thimmesch et al 29 analyzed 97 children with PPE/PE in a retrospective single-center observational study of whom 55 received methylprednisolone as a rescue therapy. Children receiving steroids had fewer chest tube insertions (62% vs. 81%, P = 0.041) but no differences were observed in total length of fever or hospital length of stay.…”
Section: Anti-inflammatory Treatmentmentioning
confidence: 99%
“…The evidence available on children is scarce, leading to great heterogeneity in clinical practice. The modalities of the antibiotic therapy and the indications and modalities of drainage procedures (chest tube alone, video‐assisted thoracoscopy [VATS] or thoracotomy, with or without fibrinolysis) vary widely from one center to another 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…However, in children, a randomized controlled trial of 60 patients with parapneumonic pleural effusion (only 22 with documented PI) showed that the addition of intravenous dexamethasone (0.25 mg/kg/dose) every 6 h over a period of 48 h reduced median recovery time (a clinical composite criterion including apyrexia and normal breathing) by 2.8 days) 21 . More recently, a Belgian center reported its experience of using corticosteroids as a rescue therapy when antibiotics and pleural drainage were considered a failure 6 . Among the 97 children with parapneumonic effusion (only 50 with documented PI), they used methylprednisolone (2 mg/kg/day) in 55 children after a median time (interquartile range [IQR]) of 5.5 (4−7) days after hospitalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation